India’s G20 Presidency and IBSA Troika – Reaffirming Southern Leadership - (:unkn) unknown (CUPEA, 2024)
India's G20 presidency has been a successful moment in global governance deliberations in the backdrop of geopolitical fragmentation and ongoing conflicts. With the unanimous adoption of the New Delhi Leaders' Declaration on the first day of the Leaders’ Summit, India was able to showcase its diplomatic effectiveness; which generated goodwill for India as a trusted partner of the Global South given the fact that G20 so far had partial representation of developing countries
Keywords: India, G20, IBSA